Three Levels of Marketing: Random, Routine, and Reflective - Perry, James F. (Ekonomika, 2002)
In the past, scarce resources have led us sort ourselves as if we were many kinds of beings, mostly unreflective, instead of one. Now, our very survival depends on classifying all people as human and reflective. This maturing change is already happening because high-tech weapons are not a scarce resource and the alternative is death by terrorism. The marketplace of the 21st century will profit by showing respect for consumers as reflective human beings. This paper offers a guide to the reflective level of thought and action, showing and explaining the logical and pragmatic relations between random, routine, and reflective functioning.